Analisis Faktor-Faktor Penerimaan Sistem Informasi Aliran Barang Dengan Menggunakan Model TAM (Technology Acceptance Model) - Andri Wijaya (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
In the current era of globalization, the development ofinformation technology has been very rapid. One of the uses ofinformation technology and information systems in the business sector of distribution of medical devices is the application of information systems and information technology that functions tomonitor and monitor the circulation of goods and the presence ofgoods. The information system has been implemented in companiesthat have been distributors of medical devices in the city ofPalembang within 3 (three) years. Therefore the authors willcontinue from previous research to find factors that influence theacceptance of technology and information systems using the TAM(Technology Acceptance Model) model and are based that systemusers tend to use the system if the system is easy to use andbeneficial to it. Therefore, after conducting this research, it isfound that the variables owned by the TAM model, namely thevariable perceived usefulness and perceived easy of use partially(individually) affect the user in using the information system aswell as the two variables simultaneously influential as well. Withthese results it can be concluded that the information flow systemused is sufficient to meet several principles of a good informationsystem that is easy to use and useful.